Comparative analysis of FACT devices for optimal improvement of power quality in unbalanced distribution systems - Ahmed M. Elkholy; Dmitry I. Panfilov; Ahmed E. ELGebaly (Scientific Reports)
Abstract This study examines the performance of asymmetric three-phase distribution systems under the influence of FACT deives such as a static VAR compensator (SVC) and a unified power controller (UPC). Each suggested device’s operating principle is developed in this paper in order to provide the best model to be used in the power flow analysis. The performance of the IEEE-13 bus imbalanced distribution model is investigated using the Newton-Raphson method. To improve network asymmetry, an optimization analysis is carried out to ascertain how each proposed device will work. In this paper, the mode of operation of each device is determined every hour to flow the changing in loads according to their daily load curve. The genetic algorithm (GA) is utilized to determine the contribution of the unified flow controller to balance the loads between phases. The multi-objective function is constructed to combine the total system losses and the average voltage unbalance coefficient. The paper provides an optimal dynamic technique to optimally operate the unified power flow controller installed in the unbalanced three-phase distribution system.